2021
DOI: 10.1519/jsc.0000000000004188
|View full text |Cite
|
Sign up to set email alerts
|

Player Position Affects Relationship Between Internal and External Training Loads During Division I Collegiate Female Soccer Season

Abstract: Ishida, A, Travis, SK, Draper, G, White, JB, and Stone, MH. Player position affects relationship between internal and external training loads during Division I collegiate female soccer season. J Strength Cond Res 36(2): 513-517, 2022-The purpose of this study was to investigate how competition phase and player position affect the relationship between internal and external training loads (ITL and ETL, respectively) in collegiate female soccer. Seventeen players participated (21.8 6 1.7 years; 165.1 6 6.2 cm; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Total sprint distances covered during match-play for DI athletes varies throughout the literature, ranging from 86 m ± 81 m [ 30 ] to 401 m ± 158 m [ 10 ] to 747 m ± 387 m [ 27 ] per match, due to differing definitions of speeds designated as a “sprint” (definitions include ≥22 kph [ 30 ], >10 kph [ 10 ], >18 kph [ 27 ],). Per position, forwards had sprint (>18 kph) distances between 608 m ± 199 m [ 26 ] and high-speed running (>15 kph) distances of 682 m ± 492 m [ 12 ], midfielders covered between 256 m ± 75 m [ 26 ] and 595 m ± 428 m [ 12 ], and defenders had the widest range with 277 m ± 61 m [ 26 ] to 734 ± 367 m [ 12 ] per match. The larger variation in sprint distances for midfielders and defenders is due to different definitions of sprint/high speed and player descriptions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total sprint distances covered during match-play for DI athletes varies throughout the literature, ranging from 86 m ± 81 m [ 30 ] to 401 m ± 158 m [ 10 ] to 747 m ± 387 m [ 27 ] per match, due to differing definitions of speeds designated as a “sprint” (definitions include ≥22 kph [ 30 ], >10 kph [ 10 ], >18 kph [ 27 ],). Per position, forwards had sprint (>18 kph) distances between 608 m ± 199 m [ 26 ] and high-speed running (>15 kph) distances of 682 m ± 492 m [ 12 ], midfielders covered between 256 m ± 75 m [ 26 ] and 595 m ± 428 m [ 12 ], and defenders had the widest range with 277 m ± 61 m [ 26 ] to 734 ± 367 m [ 12 ] per match. The larger variation in sprint distances for midfielders and defenders is due to different definitions of sprint/high speed and player descriptions.…”
Section: Resultsmentioning
confidence: 99%
“…In order to implement evidence-based training practices and optimize training stress, understanding the physical demands of a sport is critical. Considering the sport of soccer, match-play data can provide objective measures of match-play demands, can reveal positional differences during match play, can help coaches identify changes in performance over time, and can help guide player management strategies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Objective data for match-play demands (also referred to as external load, which includes total distance, sprint distance, top speed, number of sprints/explosive efforts, and Player Load, among others) are relatively easy to capture with GPS microtechnology which has become commonplace in professional and collegiate settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the suggested positional differences in physical demands, we investigated whether the team's staff may potentially need to adjust their calculations based on position in order to accurately assess internal training load 19,24,35 . A recent investigation by Ishida et al 35 , aimed to verify how competition phase and athlete position affect the relationship between internal and external training loads. The authors concluded that athlete position affects the relationship between internal and external training loads during collegiate women's soccer matches 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation by Ishida et al 35 , aimed to verify how competition phase and athlete position affect the relationship between internal and external training loads. The authors concluded that athlete position affects the relationship between internal and external training loads during collegiate women's soccer matches 35 . In the current study, TD was strongly positively correlated with sRPE-TL using 'minutes played' in the defender group.…”
Section: Discussionmentioning
confidence: 99%